Acute Arthrodesis of Lisfranc Injuries. Issue 1 (March 2019) - Kuhn, Kevin; Renninger, Christopher; Cochran, Grant; Bellamy, Joseph
Abstract : The management of acute Lisfranc injuries with tarsometatarsal joint instability has evolved over decades of experience. Arthrodesis historically has been reserved for use as a salvage procedure after development of symptomatic midfoot arthritis or failure of open reduction internal fixation (ORIF) with midfoot collapse; however, recent level I evidence has demonstrated that Lisfranc injuries managed with acute arthrodesis have comparable outcomes when compared with ORIF with less repeat procedures. We describe our technique for surgical management of acute Lisfranc injuries, both high-energy and low-energy variants, with primary arthrodesis. Satisfactory outcomes and complications of this treatment have been shown to be equivocal, if not better, than ORIF for the treatment of acute injuries. Level of Evidence: Treatment Benefits. Level V. See Instructions for Authors for a complete description of levels of evidence.